Pengaruh Price Earning Ratio, Debt To Equity Ratio, dan Return On Equity terhadap Return Saham pada Industri Perkebunan yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2017 - Dwi Wanda Pratiwi (Science of Management and Students Research Journal (SMS), 2020)
This study aims to examine the Effect of Ratio Earning (PER) Prices, Debt to Equity Ratio (DER) and Return On Equity (ROE) on Stock Returns Listed on the Indonesia Stock Exchange (IDX) for the 2012-2017 Period. With Price Rtaio Earning average is 16.384%, the average Debt to Equity Ratio is 0.434%, the average Return On Equity is 8.63%, and the average Stock Price is 2.687%.The analytical method used is multiple linear regression analysis, classic assumptions (Normality, multicoline, heteroscedacity, and autocorrelation) testing hypotheses (F test and t test) and coefficient of determination. After that the research data is processed using the SPSS version 20.0 for Windows application.Based on the calculation of Price Earning Ratio (PER), Debt to Equity Ratio (DER), and Return on Equity (ROE) quite well in the requirements of multiple linear regression from the results of sample calculations the average financial ratio for six years, the equation Y = 185.996 + 0.254X_1 + (11,685) X_2 + (0,928) X_3 for the test obtained by the F test (simultaneous), it is known that the significant results of the F_count test are more than F table (1,448> 3,24). Based on the t test, it is known that Price Earning Ratio (PER) partially does not have a significant effect on stock returns, because F_count is less than F table (0.850 <2.120) so this means H_0 is accepted and H_a is rejected. Debt to Equity Ratio (DER) partially does not have a significant effect on stock returns, because F_count is less than F table ((1,299) <2,120) this means that H_0 is accepted and H_a is rejected. Partial return on Equity (ROE) does not have a significant effect on stock returns, because F_count is less than F table ((1,485) <2,120) This means that H_0 is accepted and H_a is rejected.